Unravelling the World-Wide Pollution-Haven Effect - Grether, Jean-marie; Mathys, Nicole; de Melo, Jaime (My University, 2012)
This paper tackles the ?pollution haven? argument by estimating the pollution content of imports (PCI). The PCI is then decomposed into three components: (i) a ?deep? component (i.e. traditional variables unrelated to the environmental debate); (ii) a factor endowment component and (iii) a ?pollution haven? component reflecting the impact of differences in environmental policies. The estimation is carried out for 1987 for an extensive data set covering 10 pollutants, 48 countries and 79 ISIC four-digit sectors. Decompositions based on cross-section econometric estimates suggest a significant pollution haven effect, which increases the PCI of the North because of stricter environmental regulations in the North. At the same time, the factor endowment effect lowers the PCI of the North, as the North is relatively well-endowed in capital and pollution-intensive activities are capital intensive. On a global scale, because the bulk of trade is intra-regional with a high North-North share, these effects are small relative to the ?deep? determinants of the worldwide PCI. Robustness checks performed on a more recent dataset, but limited to sulphur dioxide, confirm these results. In sum, differences in factor endowments and environmental policies only marginally affected the PCI of world trade at the end of the 1980s.
Keywords: carbon leakage; climate change; trade policy